El estrés laboral y su influencia en el desempeño laboral de los trabajadores de la gerencia de desarrollo económico y social de la Municipalidad Distrital de Punchana Maynas Loreto 2019 - Rios Depaz, Tatiana Celeste (2023)
The present research work entitled: Work stress and its influence on the work performance of the workers of the Economic and Social Development Management of the District Municipality of Punchana, Maynas, Loreto - 2019, has set out as a general objective to determine the influence of work stress in the work performance of the workers of the Economic and Social Development Management of the District Municipality of Punchana, Maynas, Loreto – 2019; research with a quantitative approach, explanatory scope and non experimental and transversal design, in which the survey has been chosen as a technique and the questionnaire as an instrument, which has been applied to a sample established by probabilistic sampling, made up of 42 workers from the referred municipality under study; The data collected has been treated with the SPSS v statistical package. 25, to contract the hypotheses, the coefficient of determination R2, recommended for non-parametric data, has been used; reaching the following conclusions: that there is an inverse and significant influence between work stress and work performance in the workers of the Economic and Social Development Management of the District Municipality of Punchana, Maynas, Loreto 2019; Likewise, it has been determined that the dimensions: physical environment, task content and work environment directly influence work performance, which is perceived as medium, the same as work stress in the District Municipality of Punchana.